2013
DOI: 10.1111/1365-2435.12137
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition during sexual maturation affects competitive ability but not reproductive productivity in burying beetles

Abstract: Summary1. Food availability can be unpredictable. When food becomes more abundant following a period of low food availability, developing larvae or juveniles often allocate resources preferentially towards increasing growth. This has important long-term effects on adult phenotypes and longevity. Despite the importance of strategic resource allocation during early development, few studies have examined how changes in resource availability during other windows of development affect reproductive strategies and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
64
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(69 citation statements)
references
References 49 publications
3
64
2
Order By: Relevance
“…Our results confirm that relative competitive ability in burying beetles is largely determined by body size (Otronen ; Hopwood et al , ; Lee et al ), which is itself primarily determined by parental response to variation in the resources available to beetles during the larval stage (i.e., carcass size; Bartlett and Ashworth ; Eggert and Müller ). Therefore, behavioral plasticity of signaling behavior in male N. vespilloides also depends upon developmental plasticity of individuals in response to variation in carcass size.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our results confirm that relative competitive ability in burying beetles is largely determined by body size (Otronen ; Hopwood et al , ; Lee et al ), which is itself primarily determined by parental response to variation in the resources available to beetles during the larval stage (i.e., carcass size; Bartlett and Ashworth ; Eggert and Müller ). Therefore, behavioral plasticity of signaling behavior in male N. vespilloides also depends upon developmental plasticity of individuals in response to variation in carcass size.…”
Section: Discussionsupporting
confidence: 83%
“…This generated variation in the social environment experienced by focal males; from good (focal male larger than competitor) to poor (focal male smaller than competitor). Previous work has shown that relative male size is the most important determinant of contest outcomes over carcasses (Hopwood et al , 2014; Lee et al ). Our experimental design replicated what is likely to happen in the wild, where there is uncertainty about the size of competitors that males will encounter in competition for breeding resources (Hopwood et al ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newly captured beetles were cleared of phoretic mites in the field (by blowing the mites off beetles using a sharp exhalation of breath directed through pursed lips). To ensure beetles were sexually mature and to reduce individual variation in nutritional status before their use in experiments, all captured beetles were housed individually in the laboratory as described in previous experiments (Hopwood et al ., ) and fed with two decapitated mealworms, Tenebrio molitor https://en.wikipedia.org/wiki/Carolus_Linnaeus, twice per week. Laboratory beetles in experiment 2 were all used on day 8 after capture; beetles used for experiment 1 were used between 7 and 13 days after capture owing to logistical constraints in the field.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated the importance of the timing of nutritional deprivation on success in adulthood [19,20], which may have independent or interactive effects on the expression of adult phenotypes. Distinct stages may often exist in the developmental processes of organisms when nutritional variation has disproportionately large effects on phenotypic expression [21], including effects on disease susceptibility in later life [22] and adaptive polyphenisms, such as the winged phase switch in pea aphids, Acyrthosiphon pisum [23] or horn elongation in dung beetles, e.g.…”
Section: Introductionmentioning
confidence: 99%